Analysis of the communication of public bodies on social networks during the DANA in Valencia: Evaluation of the timeliness and effectiveness of information to citizens - Rodríguez Hernández, Jonattan; Ortega Fernandez, Eglée (Estudios sobre el Mensaje Periodístico, 2025)
This study analyzes the institutional communication in X during the DANA that affected the Valencian Community at the end of October 2024. Its objective is to identify the key actors, evaluate the effectiveness of their messages and examine the use of visual resources, such as emoticons, in the transmission of information. To this end, a mixed methodology was used, combining quantitative and qualitative approaches to analyze 820 tweets issued by institutional profiles. An analysis of thematic clusters, diffusion patterns and interaction levels was carried out, considering the evolution of communication in the different phases of the crisis. Data extraction was carried out using the Zeeschuimer tool, and exploratory analysis was performed with Graphext and Python libraries. The results show that communication was led by Emergències 112CV, AEMET and the Guardia Civil, with a significant increase in publications in the crisis phase, but with little activity in the previous stage. The strategic use of emoticons to reinforce warning messages was identified, although their application was not homogeneous among the different agencies. The importance of strengthening preventive communication and inter-agency coordination in extreme events was highlighted. Along these lines, it is recommended to improve the issuance of early warnings, optimize the use of visual resources and adopt strategies that balance technical information with accessible and emotionally effective messages for greater citizen resilience.